Effects of STEM learning on students with autism spectrum disorder and students with intellectual disability: a systematic review and meta-analysis - Fang Da; Ying Ma; Minjie Ma; Jieyu Mao; Zijiang Weng; Chao Yang; Tingzhao Wang (Humanities & Social Sciences Communications)
Abstract Although science, technology, engineering and mathematics (STEM) education is known to benefit students with autism spectrum disorder (ASD) and students with intellectual disability (ID), its efficacy has not been fully evaluated. This systematic review and meta-analysis examined the (1) overall intervention, maintenance and generalisation effect sizes of STEM learning; (2) effectiveness of intervention methods; and (3) influence of moderating variables (age, sex, disability type, intervention setting, interventionist and intervention duration.) Based on a Web of Science search, 40 studies published between January 2010 and July 2023 were included. This study involves two distinct groups: students with ID and students with ASD. Within the ASD group, participants were subdivided into two subgroups based on comorbid ID status: ASD-ID (with comorbid ID) and ASD-no ID (without ID). STEM learning had strong overall intervention and maintenance effects on students with ID and ASD. Disability type had a moderating effect on STEM learning outcomes, students with ASD-ID having more severe impairments compared to students with ASD-no ID and those with ID alone. This study has summarised interventions suitable for different fields and types of disabilities; educators should further optimise interventions that are proven effective. Future research should continue to focus on factors affecting the STEM learning outcomes of students with ASD and students with ID to help them improve their learning experiences, better understand the world and participate in social activities.